Analisis Dampak Pendapatan, Lama Usaha, Usia Terhadap Literasi Keuangan Pelaku UMKM - Nurul Azikin; Goso; Sahrir; Rahmad Solling Hamid (Politeknik Ganesha Medan, 2023)
This study aims to determine the effect of income, length of business, and age on the financial literacy of MSME actors in the culinary sector. This type of research uses a quantitative research approach. The objects in this study are the MSME actors in the culinary sector in the Masamba sub-district, North Luwu Regency. The sample in this study was determined based on the minimum sample size, which is 10 times the number of measurement items used in the study. The analytical method used is linear regression analysis. The results of the study show that income has a significant impact on the financial literacy of MSME actors in the culinary sector. This shows that the higher the income generated, the higher the level of financial literacy. Meanwhile, based on age and length of business, there are insignificant differences in the financial literacy of MSMEs in the culinary sector.